Hubungan Bonding Attachment dengan Resiko Terjadinya Postpartum Blues pada Ibu Postpartum dengan Sectio Caesaria di Rumah Sakit Ibu dan Anak (RSIA) Srikandi IBI Kabupaten Jember (The Correlation between Bonding Attachmentand The Risk of Happen of Postpar - Dian Charla Yodatama; Ratna Sari Hardiani; Lantin Sulistyorini (Pustaka Kesehatan, 2015)
Mother with postpartum blues could love and care to her baby, but sometimes can react negatively and do not respond at all. Interaction between mother and baby will form a bond and attachment, it can be made by rooming in. The purpose of this research was to analyze the correlation between bonding attachment and the risk of happen of postpartum blues on postpartum mothers with sectio caesaria in the Srikandi IBI Mother and Child Hospital, Jember Regency. This research used analytical observation design with cross sectional approach. Sample was 47 respondents, sampling technique used non probability sampling with purposive sampling. Data was collected by questionnaires. The result shown that 17 respondents (68,0%) have lack of bonding attachment and happen of postpartum blues. The Spearman rank test shown p value=0,000; r=-0,736, which mean there was correlations between bonding attachment and the risk of happen of postpartum blues on postpartum mothers with sectio caesaria. r = -0,736, it means that there is strong correlations between bonding attachment and the risk of happen of postpartum blues on postpartum mothers with sectio caesaria. Negative (-) means that becomes less bonding attachment, the more high risk experiencing postpartum blues..   Keywords : Bonding Attachment, Postpartum Blues